FDI has benefitted the EU members from Central and Eastern Europe and can continue to do so - Zbigniew Zimny (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
Large roles of foreign firms in Central and Eastern Europe are seen as risky and disconcerting to some. They, however, largely reflect FDI contributions critical for economic development and difficult to achieve with domestic resources which can continue in the foreseeable future.
Keywords: 330